Transcriptional metabolic reprogramming implements meiotic fate decision in mouse testicular germ cells - Xiaoyu Zhang; Yan Liu; Froylan Sosa; Sumedha Gunewardena; Peter A. Crawford; Amanda C. Zielen; Kyle E. Orwig; Ning Wang (Cell Reports, 2023)
Summary: Nutrient starvation drives yeast meiosis, whereas retinoic acid (RA) is required for mammalian meiosis through its germline target Stra8. Here, by using single-cell transcriptomic analysis of wild-type and Stra8-deficient juvenile mouse germ cells, our data show that the expression of nutrient transporter genes, including Slc7a5, Slc38a2, and Slc2a1, is downregulated in germ cells during meiotic initiation, and this process requires Stra8, which binds to these genes and induces their H3K27 deacetylation. Consequently, Stra8-deficient germ cells sustain glutamine and glucose uptake in response to RA and exhibit hyperactive mTORC1/protein kinase A (PKA) activities. Importantly, expression of Slc38a2, a glutamine importer, is negatively correlated with meiotic genes in the GTEx dataset, and Slc38a2 knockdown downregulates mTORC1/PKA activities and induces meiotic gene expression. Thus, our study indicates that RA via Stra8, a chordate morphogen pathway, induces meiosis partially by generating a conserved nutrient restriction signal in mammalian germ cells by downregulating their nutrient transporter expression.